PENINGKATAN MUTU PRESTASI BELAJAR AGAMA HINDU MELALUI MODELPEMBELAJARAN KOOPERATIF DI SMPN 2 MALANG - Made Dwianan Mustawan (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Learning of Hinduism in SMPN2 Malang was chosen method or model of cooperative learning to improve the quality of learning achievement of Hindu religion. Cooperative learning can develop cooperative behavior and better relationships among students. In cooperative learning, students learn more from their friends than their teachers. Then in interaction with cooperative learning can spur the formation of new ideas and enrich the students’ intellectual development. Cooperative learning is very effective for improving tribal and ethnic relationships in mutuality classes, considering that students in SMPN 2 Malang are more dominant are Muslims. So with the cooperative model of religious learning in improving the quality of religious learning achievement is very effective done by teachers of Hindu religion.Cooperative learning has a significant effect on the widespread acceptance of racial, cultural, and religious diversity, social strata, abilities and disabilities. Improving the quality of Hindu learning achievements with cooperative models provides opportunities for students who are in the background and conditions to work interdependent on one another over shared tasks, and through the use of cooperative rewards structures, learn to respect each other